2018
DOI: 10.1186/s40623-018-0879-4
|View full text |Cite
|
Sign up to set email alerts
|

Aso volcano eruption on October 8, 2016, observed by weather radars

Abstract: An explosive eruption occurred at the Naka-dake first crater of Aso volcano at 1:46 on October 8, 2016 (JST). According to the field survey conducted by Kumamoto University, Kyoto University, the National Institute of Advanced Industrial Science and Technology, and the Japan Meteorological Agency (JMA), a large amount of ash fell in the northeast direction of Mt. Aso; in addition, ash falls were confirmed in Kumamoto, Oita, Ehime Kagawa and Okayama Prefectures. Although the eruption was not observed using a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The total mass of ash (3.2-7.5 × 10 8 kg), as estimated from the cloud height by the echoes (12,000 m) and duration of ash emission (160-220 s), is consistent with field observations (6.0-6.5 × 10 8 kg; Sato et al 2018).…”
Section: Vapor Release From the Main Crater 41 Volcanic Ash Cloud During The 2018 Eruptionsupporting
confidence: 83%
See 1 more Smart Citation
“…The total mass of ash (3.2-7.5 × 10 8 kg), as estimated from the cloud height by the echoes (12,000 m) and duration of ash emission (160-220 s), is consistent with field observations (6.0-6.5 × 10 8 kg; Sato et al 2018).…”
Section: Vapor Release From the Main Crater 41 Volcanic Ash Cloud During The 2018 Eruptionsupporting
confidence: 83%
“…In such a situation, radar observations (Syarifuddin et al 2019;Marzano et al 2020) can track an ash cloud. Sato et al (2018) presented a time-series of the ash cloud echo of the phreatic eruption at Aso volcano on 8 October 2016. The echo obtained from weather radar with a wavelength of 5.6 cm (C-Band), operated by the Japan Meteorological Agency (JMA), is consistent with the distribution of the tephra deposit.…”
Section: Vapor Release From the Main Crater 41 Volcanic Ash Cloud During The 2018 Eruptionmentioning
confidence: 99%
“…In general, secondary accumulation maxima are documented in distal regions, typically hundreds of kilometers from the volcano (e.g., the 1980 eruption of Mt. St. Helens; Sarna-Wojcicki et al 1981, June 15, 1991Weisner et al 2003, andthe August 18 andSeptember 16-17, 1992 eruptions of Mt Spurr;McGimsey RG Neal and Riley 2001). Wet aggregation could have enhanced the effective removal of airborne fine particles from the plume.…”
Section: Secondary Accumulation Maximamentioning
confidence: 99%
“…Weather radars of JMA also captured the volcanic ash cloud from the explosive eruption of Aso on October 8, 2016 (JST). Sato et al (2018) used five radars' data and found that the ash cloud travel more than 200 km away from the crater. The eruption altitude was estimated to be 12,000 m ASL ± 687 m (1σ).…”
Section: Remote Sensingmentioning
confidence: 99%